Ethanol modified supercritical fluid extraction and antioxidant activity of cajaninstilbene acid and pinostrobin from pigeonpea [ Cajanus cajan (L.) Millsp.] leaves - Kong, Yu; Fu, Yu-Jie; Zu, Yuan-Gang; Liu, Wei; Wang, Wei; Hua, Xin; Yang, Mei (Food chemistry, 2009)
Supercritical fluid carbon dioxide (SF-CO 2) extraction (SFE) of cajaninstilbene acid (CSA) and pinostrobin (PI) from pigeonpea leaves and antioxidant activity were investigated for the first time. SFE gave higher extraction yields than conventional heat-refluxing extraction (HRE) because of the severe breakage of cell morphology caused by SF-CO 2, which was observed by scanning electron microscopy (SEM). CO 2 flow rate, modifier composition and liquid to solid ratio were firstly optimised, 12 kg/h, and 80% EtOH with a liquid to solid ratio of 10 ml/g raw material exhibited better extraction performance. Then a central composite design (CCD) combined with response surface methodology was used to study the effects of extraction pressure, temperature and time on the extraction yields of CSA and PI, the optimal parameters were 30 MPa, 60 °C and 2 h. An antioxidant activity investigation showed SFE extracts exhibited better free radical-scavenging activity than HRE extracts with an IC 50 value of 0.2259 mg/ml.